Developing the skill of laryngeal mask insertion - Mohr, Stefan; Weigand, Markus A.; Hofer, Stefan; Martin, Eike; Gries, A.; Walther, A.; Bernhard, Michael (Der Anaesthesist, 2013)
Laryngeal mask insertion (LMI) represents a fundamental skill for anesthesiologists in routine management as well as in difficult airway situations. This study aimed to evaluate the time needed by first year anesthesiology residents to perform 40 LMIs and assessed the associated success rates and the number of attempts needed for successful LMI.
Gesehen am 25.05.2021